Improved numerical modeling of morphodynamics of rivers with steep banks. (July 2016) - Langendoen, Eddy J.; Mendoza, Alejandro; Abad, Jorge D.; Tassi, Pablo; Wang, Dongchen; Ata, Riadh; El kadi Abderrezzak, Kamal; Hervouet, Jean-Michel
Highlights: A physically- and process-based bank erosion model is coupled with TELEMAC2D/SISYPHE. The model includes the effects of subgrid-scale riverbank geometry. The model is tested for meandering-river planform adjustment. The model simulates a great variety and complexity in meander wavelengths. Planform adjustment rate is reduced if alternate bar and meander wavelength are similar. Abstract: The flow and sediment transport processes near steep streambanks, which are commonly found in meandering, braided, and anastomosing stream systems, exhibit complex patterns that produce intricate interactions between bed and bank morphologic adjustment. Increasingly, multi-dimensional computer models of riverine morphodynamics are used to aid in the study of these processes. A number of depth-averaged two-dimensional models are available to simulate morphologic adjustment of both bed and banks. Unfortunately, these models use overly simplified conceptual models of riverbank erosion, are limited by inflexible structured mesh systems, or are unable to accurately account for the flow and sediment transport adjacent to streambanks of arbitrary geometry. A new, nonlinear model is introduced that resolves these limitations. The model combines the river morphodynamics computer models TELEMAC-2D and SISYPHE of the open source TELEMAC-MASCARET suite of solvers with the bank erosion modules of the CONCEPTS channel evolution computer model. The performance of the new model is evaluated for meander-planform initiation and development. The most important findings are: (1) the model is able to simulate a much greater variety and complexity in meander wavelengths; (2) simulated meander development agrees closely with the unified bar-bend theory of Tubino and Seminara (1990); and (3) the rate of meander planform adjustment is greatly reduced if the wavelength of alternate bars is similar to that of meanders.